NAVIGATING TURBULENT WATERS: HOW MSMES LEVERAGE ORGANIZATIONAL ADAPTABILITY AND STRATEGIC RENEWAL FOR BUSINESS RESILIENCE - Muhammad Husni Tamrin (Generate Digital Publishing, 2025)
Objective: his study aims to examine how Micro, Small, and Medium Enterprises (MSMEs) with limited resources in emerging markets cope with extreme macro-environmental shocks. This study challenges the conventional, Western-centric, and asset-based resilience paradigm by conceptualizing new dynamic mechanisms for corporate survival and transformation. Research Design & Methods: This study employs a multiple inductive qualitative case study design. By analyzing the real-time crisis response trajectories of five distinct MSMEs in emerging market contexts, data were collected through semi-structured in-depth interviews, field observations, and archival records, and subsequently analyzed using systematic thematic coding. Findings: This study conceptualizes a new sequential evolutionary model, termed the Processual Agility Framework. Transformative resilience (bounce forward) is not determined by the ownership of static assets, but rather by a two-stage process: Short-term Organizational Adaptability (driven by cognitive flexibility and tactical resource bricolage) acts as a critical liquid buffer that directly facilitates long-term Strategic Renewal (carried out through radical business model experimentation and market reorientation). Relying solely on short-term adaptation traps companies in vulnerable survival. Implications & Recommendations: For managers, crisis mitigation requires overcoming cognitive rigidity and aggressively rejecting legacy burdens to experiment with digital value architectures. For policymakers, interventions must shift from passive financial aid toward capacity-building programs that foster grassroots digital agility, cognitive flexibility, and open-source resource integration. Contribution & Value Added: This paper significantly advances Dynamic Capabilities Theory by demonstrating that small-scale capabilities operate through micro-cognitive foundations, not formal corporate routines. Furthermore, this paper elevates resource bricolage from a negatively viewed survival tactic to an intentional strategic enabler within institutional vacuums, shifting the global literature’s focus from asset-based recovery to processual agility.